2022
DOI: 10.3889/oamjms.2022.9508
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Fasting and its Health Benefits: What’s New?

Abstract: Fasting is one of the five pillars of Islam. Fasting entails more than abstaining from food and drink, fasting improves impulse control and aids in the development of good behavior. The holy month of Ramadan falls on the 9th month of the lunar calendar. Ramadan is a month-long fasting period that takes place between dawn and sunset. Some people with diabetes and those who are sick or have certain medical conditions may be exempt. The majority of people with diabetes, on the other hand, choose to fast; even aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Fasting can be seen as an example of a practice emphasized in Islam. Fasting serves two purposes: fulfilling duty and personal growth by cultivating self-discipline, adaptability, and patience in response to urges or desires (Hossain, 2012;Pakkir Maideen et al, 2017;Rahman, 2022). Fasting can impact an individual's self-control, especially when it comes to well-being (Hidayati, 2020;Rahmi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fasting can be seen as an example of a practice emphasized in Islam. Fasting serves two purposes: fulfilling duty and personal growth by cultivating self-discipline, adaptability, and patience in response to urges or desires (Hossain, 2012;Pakkir Maideen et al, 2017;Rahman, 2022). Fasting can impact an individual's self-control, especially when it comes to well-being (Hidayati, 2020;Rahmi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle changes during Ramadan may reduce cardiovascular disease risk factors in both obese and normalweight adults via a reduction in body mass and improvements in blood lipid profiles [35,50]. Lifestyle changes may positively improve health and well-being [51][52][53][54][55]. One study reported no significant change to PA levels in university students during Ramadan compared to the pre-Ramadan period [2].…”
Section: Lifestyle Changes During Ramadanmentioning
confidence: 99%
“…All Muslims who fast the holy month of Ramadan have metabolic changes as a result of these alterations [1] .Many Muslim patients with acute or chronic medical conditions prefer fasting. Religiosity, personal beliefs, and spirituality are crucial factors of the social determinants that impact health-related behaviors and treatment adherence of patients [2,3] .…”
Section: Introductionmentioning
confidence: 99%